2015
DOI: 10.1038/ncomms10221
|View full text |Cite
|
Sign up to set email alerts
|

H19 lncRNA alters DNA methylation genome wide by regulating S-adenosylhomocysteine hydrolase

Abstract: DNA methylation is essential for mammalian development and physiology. Here we report that the developmentally regulated H19 lncRNA binds to and inhibits S-adenosylhomocysteine hydrolase (SAHH), the only mammalian enzyme capable of hydrolysing S-adenosylhomocysteine (SAH). SAH is a potent feedback inhibitor of S-adenosylmethionine (SAM)-dependent methyltransferases that methylate diverse cellular components, including DNA, RNA, proteins, lipids and neurotransmitters. We show that H19 knockdown activates SAHH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(217 citation statements)
references
References 51 publications
9
208
0
Order By: Relevance
“…Our research has revealed that high expression of H19 in breast cancer attenuates cell apoptosis normally seen in response to chemotherapy. Other studies have reported that H19 promotes the progression and metastasis of tumors in different ways, by serving as a miRNA sponge, by altering DNA methylation, and by controlling mRNA decay [10, 18, 19]. In the present paper, we have demonstrated an epigenetic inhibition of pro-apoptotic gene BIK by the association of H19 with the histone methyltransferase EZH2.…”
Section: Introductionsupporting
confidence: 63%
“…Our research has revealed that high expression of H19 in breast cancer attenuates cell apoptosis normally seen in response to chemotherapy. Other studies have reported that H19 promotes the progression and metastasis of tumors in different ways, by serving as a miRNA sponge, by altering DNA methylation, and by controlling mRNA decay [10, 18, 19]. In the present paper, we have demonstrated an epigenetic inhibition of pro-apoptotic gene BIK by the association of H19 with the histone methyltransferase EZH2.…”
Section: Introductionsupporting
confidence: 63%
“…iLet7s are chemically modified oligonucleotides that specifically bind to let-7 and inhibit its activity. The rationale for including iLet7 was to confirm the contribution of let-7 to the H19-mediated pathway, as H19 has other functions besides sequestering let-7 [1013, 23]. Thus, in the presence of iLet7, we would expect that the effects of H19 knockdown on EVT would be attenuated, as iLet7 would neutralize let-7 released from H19 sequestration.…”
Section: Resultsmentioning
confidence: 99%
“…The incomplete restoration of TβR3 expression by iLet7 was not surprising given that H19 is a multifunctional lncRNA. We have recently reported that H19 alters gene methylation genome-wide through modulation of the S-adenosylhomocysteine hydrolase activity [23], including H19 knockdown-induced hypomethylation of TβR3 in the intron region [23]. It remains to be tested whether downregulation of H19 in human trophoblast cells might induce methylation changes in the TβR3 gene, which may explain the partial restoration of TβR3 expression by iLet7.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on H19 function in cancer show both oncogenic and tumor suppressive effects (Medrzycki et al, 2014, Barsyte-Lovejoy et al, 2006, Hao et al, 1993, Juan et al, 2000). The reported H19 activities are diverse, including interaction with epigenetic regulators (Monnier et al, 2013, Giovarelli et al, 2014, Zhou et al, 2015, Luo et al, 2013), regulation of microRNAs as competing endogenous RNA (ceRNA) (Yan et al, 2015, Imig et al, 2015, Kallen et al, 2013, Liang et al, 2015), or production of miR-675 as a primary transcript (Keniry et al, 2012, Venkatraman et al, 2013, Zhu et al, 2014, Shi et al, 2014, Tsang et al, 2010). …”
Section: Introductionmentioning
confidence: 99%